Connecting lignin-degradation pathway with pre-treatment inhibitor sensitivity of Cupriavidus necator - Wang, Wei; Yang, Shihui; Hunsinger, Glendon B.; Pienkos, Philip T.; Johnson, David K. (Frontiers in Microbiology, 2014)
To produce lignocellulosic biofuels economically, the complete release of monomers from the plant cell wall components, cellulose, hemicellulose and lignin, through pretreatment and hydrolysis (both enzymatic and chemical), and the efficient utilization of these monomers as carbon sources, is crucial. In addition, the identification and development of robust microbial biofuel production strains that can tolerate the toxic compounds generated during pretreatment and hydrolysis is also essential. In this work, Cupriavidus necator was selected due to its capabilities for utilizing lignin monomers and producing polyhydroxylbutyrate (PHB), a bioplastic as well as an advanced biofuel intermediate. We characterized the growth kinetics of C. necator in pretreated corn stover slurry as well as individually in the presence of 11 potentially toxic compounds in the saccharified slurry. We found that C. necator was sensitive to the saccharified slurry produced from dilute acid pretreated corn stover. Five out of 11 compounds within the slurry were characterized as toxic to C. necator, namely ammonium acetate, furfural, hydroxymethylfurfural (HMF), benzoic acid, and p-coumaric acid. Aldehydes (e.g., furfural and HMF) were more toxic than the acetate and the lignin degradation products benzoic acid and p-coumaric acid; furfural was identified as the most toxic compound. Although toxic to C. necator at high concentration, ammonium acetate, benzoic acid, and p-coumaric acid could be utilized by C. necator with a stimulating effect on C. necator growth. Consequently, the lignin degradation pathway of C. necator was reconstructed based on genomic information and literature. The efficient conversion of intermediate catechol to downstream products of cis,cis-muconate or 2-hydroxymuconate-6-semialdehyde may help improve the robustness of C. necator to benzoic acid and p-coumaric acid as well as improve PHB productivity.